UHPLC-MS/MS Analysis of the Accumulation and Excretion of Steroidal Glycoalkaloids Consumed by Potato Tuber Moth (Phthorimaea operculella) Larvae under Different Feeding Treatments - Yajin Li; Qiong Wang; Xiaoyu Xu; Huachun Guo (Insects, 2022)
Food poisoning caused by potato glycoside alkaloids (SGA) remains a critical factor that affects potato production safety. The potato tuber moth (Phthorimaea operculella) is a notorious pest that displays good adaptability to SGA in potato tissues. Studies that explore the mechanisms underlying SGA homeostasis in potato tuber moth larvae are urgently needed. In this study, ultra-high-performance liquid chromatography (UHPLC)-triple quadrupole mass spectrometry (MS/MS) was applied to detect the dominant SGA substances α-solanine and α-chaconine in potato leaves and PTM larval tissues. From the highest to lowest SGA concentrations, the potato cultivars studied were ranked as follows: DS47, LS6, DS23 and QS9. To exclude the influence of nutrients within different potato varieties, different SGA containing (0%, 0.1%, 0.2%, 0.3% and 0.4%) the artificial diet treatment groups were added. DS47 and 0.3% SGA-containing artificial diets presented the best conditions for PTM growth, development and reproduction compared to other potato cultivars and artificial diet controls. The potato tuber moth larva tissues were dissected and the SGA content within different tissues were detected using an UHPLC machine. The results showed that α-chaconine was dispersed in the feces, midgut, hindgut, head and cuticle, and α-solanine was distributed only in the feces and midgut. Antibiotic-treated insects exhibited higher concentrations of SGA than the normal microbiome group. Furthermore, the SGA concentrations of 100 newly-hatched PTM larvae and puparia were detected, with both of them found to contain small amounts of SGA. The results showed that ecdysis and the excretion process were effective approaches used by the potato tuber moth to equilibrate internal SGA accumulation. The microorganism-decreased SGA concentrations were excited in their gut. SGA may transfer from adults to the next generation, and SGAs in PTM are inheritable. In this study, we demonstrated that the potato tuber moth possessed an effective method to preliminarily decrease high SGA accumulation in potato.